2012
DOI: 10.5293/ijfms.2012.5.2.065
|View full text |Cite
|
Sign up to set email alerts
|

Application of Gurney Flaps on a Centrifugal Fan Impeller

Abstract: The objective of the present investigation is to explore the possibility of improving the performance of a centrifugal fan at low Reynolds numbers using a simple passive means, namely Gurney flap (GF). GFs of 1/8 th inch brass angle (3.175 mm) corresponding to 15.9% of blade exit height or 5.1% of blade spacing at the impeller tip are attached to the impeller blade tip on the pressure surface. Performance tests are carried out on the centrifugal fan with vaneless diffuser at five Reynolds numbers (viz., 0.30, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Recently Nilavarasan et al (2019) performed computational investigations on NACA 0010 cascade using Gurney Flaps with different inclinations at different stagger angles. Dundi et al (2012) experimentally demonstrated that application of Gurney flap to the tip of a centrifugal impeller blade improves the performance at low Reynolds number. Suresh and Sitaram (2019) tested the same centrifugal fan with three types of Gurney flaps, angle, quarter round and half round types of different heights at different Reynolds numbers and found that quarter round Gurney flap gives slightly improved performance compared to the other two types.…”
Section: Motivationmentioning
confidence: 99%
“…Recently Nilavarasan et al (2019) performed computational investigations on NACA 0010 cascade using Gurney Flaps with different inclinations at different stagger angles. Dundi et al (2012) experimentally demonstrated that application of Gurney flap to the tip of a centrifugal impeller blade improves the performance at low Reynolds number. Suresh and Sitaram (2019) tested the same centrifugal fan with three types of Gurney flaps, angle, quarter round and half round types of different heights at different Reynolds numbers and found that quarter round Gurney flap gives slightly improved performance compared to the other two types.…”
Section: Motivationmentioning
confidence: 99%
“…lift coefficient depends on airfoil shape [89] 2012 Gurney flap Centrifugal fan 15.9%b 2 30,000-82,000 Pressure ratio and operating range improved at Re < 69,000 [81] 2012 Gurney flap 3-7%c 20,000-35,000 Lift augmentation [90] 2011 Gurney flap Axial fan 10, 20, 30%c < 100,000 Max 18% increase in efficiency with q v,max [83] 2011 Gurney flap 0.7-6%c 254,000 Lift and drag augmentation [91] 2011 Gurney flap 1-6%c 105,000 Wake vortex control [92] 2011 Gurney flap 1.5%c 2,100,000 Vibration reduction [93] 2010 Jet-flap LPT cascade 25,000-200,000 12.5% reduction in solidity [94] 2010 Gurney flap LPT cascade 0.5-3%c 25,000-200,000 12.5% reduction in solidity [8] 2010 Microtab Wind turbine 1-1.5%c 460,000 Max 37% increase in lift [35] 2010 Gurney flap 3000-20,000 Lift augmentation [95] 2010 Gurney flap 40,000-80,000 Lift augmentation [96] 2003 Gurney flap Turbine cascade 0.6-2.7%c 28,000-167,000 Max 9% increase in lift force [85] 2000 Gurney flap 0.5-2%c 1,000,000 Increased lift and drag Outcome: Lift augmentation…”
Section: Gurney Flaps (Classification: Passive Geometric)mentioning
confidence: 99%
“…However both static and total pressure efficiencies for fan with Gurney flap are reduced compared with those of the fan without Gurney flap. Dundi et al (2012) investigated the effect of Gurney flap on a centrifugal fan with different Reynolds numbers. Energy coefficient increased with Gurney flap, dominantly at low Reynolds number and maximum flow rate slightly increased for the fan with a Gurney flap.…”
Section: Introductionmentioning
confidence: 99%
“…Energy coefficient increased with Gurney flap, dominantly at low Reynolds number and maximum flow rate slightly increased for the fan with a Gurney flap. Based on the encouraging results of Dundi et al (2012) further investigations were undertaken to optimize the height of Gurney flap by Suresh and Sitaram (2014) for application in centrifugal fans and found that there is an optimal Gurney flap height at which performance of the fan increases substantially. Kim et al (2013 and had recently applied a 5% chord height Gurney flap to the tip of a radial fan impeller for an air conditioner fan.…”
Section: Introductionmentioning
confidence: 99%